Ikhtilaf 'Ulama al-Madzahib al-Fiqhiyah al-Islamiyah fi Hukm Ram al-Jumar fi al-Lail wa Qabl al-Zawal fi Ayam al-Tasyriq Dirasah Tahliliyah - Hudzaifah Achmad Qotadah; Adang Darmawan Achmad (AL-MUFASSIR, 2021)
The Hajj is an annual Islamic pilgrimage to Mecca and is the fifth pillar of Islam, though all Muslims believe that these five pillars of Islam are indeed the foundation of Islam. Hajj has become a compulsory religious obligation for Muslims, that must be conducted at least once in a lifetime by all muslims Around the world who has all the abilities in financial, physical, and psychological terms. One of the duties during Hajj is the throwing of the Jamarat, but there was a disagreementbetween Muslim scholars regarding throwing the Jamarat at night and before noon in the days of Tashreeq. This topic's objective is to examine the difference of Islamic scholar-based four madhahib of fiqh regarding the ruling of throwing Jamarat at night and before noon in the days of Tashreeq.